TELATAH PERILAKU: UPAYA PREVENTIF MENJAGA PERANGAI ANAK MUDA MENURUT 1 KORINTUS 6:19,20 - Stimson Hutagalung (Unika Santu Paulus Ruteng, 2022)
It is important to keep the body healthy, because the body is the temple of God. In fact, many young people do not take care of their bodies by eating and drinking foods that damaging the body without them knowing it. The purpose of this study is to analysed the extent to which young people can be tempestuous and curb their passions for the use of tobacco, liquor and drugs, their understanding of the body as the temple of the Holy Spirit, and obtain preventive measures so that young people can control their passions. The research method used is a qualitative method with a descriptive approach. A descriptive approach was taken to get a general idea of ​​the extent to which young people's understanding of temperance and the body is the temple of God through their actions by not smoking, drinking, and taking drugs. Data collection techniques using questionnaires and interviews. Questionnaires were distributed to students and senior high school students at Adventist Schools in Jakarta. The results of the descriptive questionnaire and the results of the interviews were then analysed to find out what preventive measures can be taken by educators, namely parents and teachers, so that young children can maintain their lusts and keep their bodies as temples of God. The novelty of this research is that teachers, pastors, parents can participate in helping young people take care of their bodies with preventive efforts by empowering, trusting, supporting, accompanying them